Sustainable Economic Model for Islamic Boarding Schools: The Role of Sharia Cooperatives, Halal Certification, and Digital Transformation - Ainurrohmah, Syifa’; Rahmawati, Yunaita (Inovasi Analisis Data, 2025)
Objective: The role of integrated economic models on Islamic higher education institutions is to be evaluated in this paper, based on the interdependence of cooperative agribusiness principles, cooperative networks, and cooperative certification systems for sustainable development.Methods: The study design is a cross-sectional survey study. It uses a quantitative approach. This includes multiple regression and hierarchical moderation analysis. Data were collected using structured questionnaires to measure constructs related to economic models, institutional collaboration, and certification frameworks, and these were subjected to appropriate reliability and validity tests.Results: The results indicate robust positive correlations between the central economic framework and sustainability outcomes within institutions. Collaboration among multiple stakeholders will be essential for organizational and participant development. According to the study, these relationships are much stronger thanks to leadership support, specialized knowledge, and technological adoption, forming an ecosystem for sustainable development.Novelty: The novel integrated framework presented in this research successfully bridges traditional values with contemporary economic practices. It introduces unique moderating mechanisms that enhance the effectiveness of core institutional strategies. The study is pioneering in its approach, showing how ethical principles can be integrated with modern development methods in a systematic way.Research Implication: Educational leaders seeking to balance traditional values with economic sustainability will find the findings valuable, as they provide evidence-based strategies for institutional development. Contributions have been made to broader discussions on sustainable educational models by the research, and significant relevance has been demonstrated for institutions navigating the intersection of tradition and modernity.